2006
DOI: 10.1523/jneurosci.2064-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Disorganization in Hippocampus: A Physiological Model of the Disorganization in Psychosis

Abstract: Cognitive coordination refers to processes that organize the timing of activity among neurons without altering individual discharge properties. Coordinating processes allow neural networks to coactivate related representations and prevent the coactivation of unrelated representations. Impaired cognitive coordination, also called cognitive disorganization, is hypothesized to be the core deficit in the disorganized syndrome of schizophrenia (Phillips and Silverstein, 2003), a condition characterized by hallucina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 64 publications
10
106
1
Order By: Relevance
“…Clozapine had the highest number of genes changed in the VT. Nevertheless, a disproportionate number of higher-probability, category I genes were in the HIP, consistent with a likely central role of this region in the pathophysiology of schizophrenia and related disorders [Callicott et al, 2005;Gisabella et al, 2005;Holt et al, 2005;Katsel et al, 2005a,b;Benes et al, 2006;Kuroki et al, 2006;Olypher et al, 2006;Tanabe et al, 2006;Vita et al, 2006] (Fig. 2).…”
Section: Number Of Genessupporting
confidence: 56%
“…Clozapine had the highest number of genes changed in the VT. Nevertheless, a disproportionate number of higher-probability, category I genes were in the HIP, consistent with a likely central role of this region in the pathophysiology of schizophrenia and related disorders [Callicott et al, 2005;Gisabella et al, 2005;Holt et al, 2005;Katsel et al, 2005a,b;Benes et al, 2006;Kuroki et al, 2006;Olypher et al, 2006;Tanabe et al, 2006;Vita et al, 2006] (Fig. 2).…”
Section: Number Of Genessupporting
confidence: 56%
“…Previous studies have shown that the hippocampus may be associated to internal inhibition and perseverative responses that contribute to impairments in new learning (Kimble 1968;Whishaw and Tomie 1997). The hippocampus has also been implicated in cognitive coordination processes (Wesierska et al 2005;Olypher et al 2006) that allow individuals to discriminate between relevant and irrelevant stimuli and that are thought to be impaired in disorganized schizophrenia (Phillips and Silverstein 2003). Indeed, the observed cognitive inflexibility in our studies is reminiscent of behavioral symptoms, such as perseveration and cognitive disorganization (manifested as an inability to discriminate between relevant vs. irrelevant stimuli), in schizophrenia, manic depression, and obsessive-compulsiveness (Morice 1990;Joseph 1999;Clarke et al 2004Clarke et al , 2005Gray and Snowden 2005;Lubow and Kaplan 2005).…”
Section: Suppression Of Nurr1 In Ca3 During Mid-acquisition Results Imentioning
confidence: 99%
“…Also, studies examining the influence of NMDA receptor antagonists on recurrent inhibition indicate that a schizophrenia-like disturbance in association patterns, and dysregulation in suppression of associations, is related to a deficit of attentional mechanisms (Nestor et al, 1998(Nestor et al, , 2001McCarley et al, 1999). The dysregulation could be closely related to defective attentional filtering and a failure to inhibit activity of irrelevant neural assemblies (Vaitl et al, 2002;Olypher et al, 2006) that may lead to pathologically increased neural complexity . It is possible that these states may implicate chaos that occurs when the neural process involves a large number of complex interlinked and simultaneously active states (Korn and Faure, 2003).…”
Section: Discussionmentioning
confidence: 99%